Pulmonary Rehabilitation and Physical Activity in COPD - Natalia Tylczyńska; Kinga Tylczyńska; Zuzanna Skiba; Jakub Skiba; Aleksandra Zielińska; Szymon Szypulski; Kinga Kowalik; Maria Michalska; Sebastian Iwaniuk; Ignacy Maciejewski (Quality in Sport)
Introduction and Purpose: Chronic obstructive pulmonary disease (COPD) is a type of progressive lung disease characterized by chronic respiratory symptoms and airflow limitation. The purpose of this study was to present pathogenesis, symptoms, diagnosis and treatment of COPD and principal strategies and types of exercises of pulmonary rehabilitation in patients with COPD.